PENGARUH DOSIS PUPUK KANDANG SAPI TERHADAP BUDIDAYA JAGUNG MANIS PADA LAHAN BERPASIR - Saijo Saijo (Fakultas Pertanian - UMJ, 2022)
The purpose of this study was to evaluate and find the effective dose of cow manure on the growth and yield of sweet corn on sandy soil. Using a 4-level randomized block design with 4 replications and 16 experimental plots. Variables observed were: plant height, number of leaves, stem diameter, fruit length, weight of cobs with cob and weight of cobs without cob. The results of the study found that the application of cow manure had a significant effect on all growth variables. While the yield component variable in the form of cob weight without husks per plant showed that a dose of 25 t ha-1 (10 kg plot-1) was the best treatment and produced a cob weight of 202.10 g plant-1.